Penerapan Procedural Content Generation untuk generasi level dalam game Mythical Maze - Hansen Krisna Putra; Liliana Liliana (Jurnal Infra, 2021)
Level design is one of the issues in creating a multi-level game application. In level design, some of the important keypoints are the variation of the level, the time to create it, and the locations of objects inside of a level, for example the player’s starting point and the exit point. Procedural Generation can be used to simplify the process of designing a level.In the implementation of Procedural Generation, the first step is to determine the size of the desired level or terrains. The size of a terrain will affect the complexity of a level, where it will affect the amount of rooms and corridors that is made. Next, rooms with various sizes are made and placed within the level with a desired pattern, which is connected by placing corridors that acts as a connector between two rooms. The last step to create a level is to place the objects inside the level, such as player character and the end point, where a distance is given between two objectsFrom the methods that are used, a level can be automatically made with multiple variations. The levels themselves are well made in which all of the rooms are connected by corridors and the player can reach the exit point from any given poinit in a level. This method always results in a terrain where there is a line or route between the starting and exit points. Each level’s difficulty is unique, that is affected by complexity, the distance between objects, and the time given to finish a level. The player doesn’t always able to finish a big level. This method can be used to produce variants of a maze, and to add the difficulty, the terrain itself can be enlargen to add complexity